Thermomechanical modeling of fiber reinforced material including interphasial properties and its application to epoxy/glass composites. Issue 4 (13th June 2016) - Bozic, Marko; Fleischhauer, Robert; Kaliske, Michael
Abstract : Purpose: – The purpose of this paper is to investigate of interphasial effects, including temperature dependency, within fiber reinforced polymers on the overall composite behavior. Providing theoretical and numerical approaches in terms of a consistent thermomechanical finite element method framework are further goals of this research. Design/methodology/approach: – Starting points for achieving the aims of this research are the partial differential equations describing the evolution of the displacements and temperature within a continuum mechanical setting. Based on the continuous formulation of a thermomechanical equilibrium, constitutive equations are derived, accounting for the modeling of fiber reinforced thermosets and thermoplastics, respectively. The numerical solutions of different initial boundary value problems are obtained by a consistent implementation of the proposed formulations into a finite element framework. Findings: – The successful theoretical formulation and numerical modeling of the thermoinelastic matrix materials as well as the thermomechanical treatment of the composite interphase (IP) are demonstrated for an epoxy/glass system. The influence of the IP on the overall composite behavior is successfully investigated and concluded as a further aspect. Originality/value: – A thermomechanical material model, suitable for finite thermoinelasticity of thermosets and thermoplastics is introduced and implemented into a novel kinematic framework in context of the inelastic deformation evolution. The gradually changing material properties between the matrix and the fiber of a composite are continuously formulated and numerically processed, in order to achieve an efficient and realistic approach to model fiber reinforced composites.